The Prognostic Value of Sequential 18F-FDG PET/CT Metabolic Parameters in Outcomes of Upper-Third Esophageal Squamous Cell Carcinoma Patients Treated with Definitive Chemoradiotherapy - Ha, Le Ngoc; Chau, Nguyen Dinh; Bieu, Bui Quang; Son, Mai Hong (World Journal of Nuclear Medicine, 2023)
Objective The aim of this study is to determine prognostic values of sequential 18F-FDG PET/CT metabolic parameters in locally advanced esophageal squamous cell carcinoma (ESCC) patients treated with definitive chemoradiotherapy.Materials and Methods Forty locally advanced ESCC patients treated with definitive chemoradiotherapy (dCRT) who received pre-treatment 18F-FDG PET/CT (PET1) and 3-months post-treatment 18F-FDG PET/CT (PET2) were enrolled in the prospective study. 18F-FDG PET parameters of the primary tumor including maximum and mean standardized uptake values (SUVmax, SUVmean), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) were calculated on PET delineated primary tumor. Using Kaplan-Meier curves to estimated overall survival (OS), progression-free survival (PFS), and local-regional control (LRC). Cox regression analysis was performed to find significant prognostic factors for survival.Results With a median follow-up of 13.5 months, the 4-year OS, PFS, and LRC rates were 67.3%, 52.6%, and 53.4% respectively. Patients with MTV 2 > 5.7 had lower OS, PFS, and LRC rates than the lower MTV 2 group (p < 0.05). Univariate Cox regression analysis showed that MTV2 was a significant prognostic factor for OS, PFS, and LRC (p < 0.05).Conclusion MTV parameter of sequential 18F-FDG PET/CT could be used as a prognostic factor for OS, PFS, and LRC in locally advanced ESCC patients treated with dCRT.
Keywords: 18F-FDG PET/CT; sequential metabolic parameter; predictive value; definitive chemoradiotherapy; esophageal squamous cell carcinoma